The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa - Gil, Marta; Ramil, Fran (Zootaxa, 2017)
This paper is the result of the study of large collections of Sertulariidae Lamouroux, 1812 (Cnidaria, Hydrozoa, Hydroidolina) obtained from continental margins of Northwest Africa by several Spanish and Norwegian surveys between 2004 and 2012. Material collected from Lusitanian seamounts by the French Seamount 1 expedition and from the Great Meteor Bank by the German survey Meteor 42/3 were also examined. A total of 12 species belonging to the genus Diphasia were studied and illustrated, and four new species were described: Diphasia leonisae n. sp., Diphasia saharica n. sp., Diphasia africana n. sp., and Diphasia anaramosae n. sp. Diphasia attenuata, Diphasia fallax and Diphasia tropica were not represented in the collections. However, they have been discussed here because they had been previously reported in the study area or in the eastern North Atlantic. One species was only identified to the genus level. The syntype material of Diphasia attenuata var. robusta Billard, 1924, neotype of Diphasia delagei Billard, 1912, and comparison material for the other species that have been preserved in several zoological collections were also examined. Besides, an identification key for these species is provided.